Do Royal Servants of Ngayogyakarta Hadiningrat Palace Speak Bagongan Language?: Bagongan Vocabularies and Its Role - Yuliati, Ria; Sajarwa, Sajarwa; Winarti, Daru (REiLA : Journal of Research and Innovation in Language, 2024)
The Ngayogyakarta Hadiningrat Palace possesses a unique linguistic tradition, characterized by the use of the Bagongan variety of Javanese. Despite its significance, there is limited research on the origins, purposes, and accurate usage of Bagongan vocabularies by the Royal Servants (Abdi Dalem) of the palace. This study aims to analyze the origin of Bagongan vocabularies, their purposes, and the proficiency of Abdi Dalem in using this linguistic variety. Employing a descriptive qualitative approach, this linguistic description research involved analyzing eleven Bagongan vocabularies. Data were collected from written and spoken forms, literature, audio-visual recordings, and interviews. The collected data were then analyzed thematically and discursively using morphological and syntactic theories. The analysis revealed that six vocabularies had undergone adoption or intact absorption: 1) manira/menira, 2) pakenira/pekenira, 3) puniki, 4) puniku/punika, 5) punapi, and 6) nedha. Additionally, five vocabularies showed changes from Old Javanese: 1) henggeh/enggeh, 2) boya/mboya, 3) wenten, 4) besaos, and 5) seyos. These vocabularies originate from old Javanese, which lacks language stratification, making it suitable as a unifying language in the palace. However, dynamics of the use of Javanese Bagongan variety due to language influences from outside the palace were noted in the use of Bagongan vocabularies, krama vocabularies, ngoko affixes, and spelling of the writing. The findings suggest the need for stricter and more binding regulations on the use of Bagongan language within the palace.